Hubungan Antara Pengetahuan dan Kemandirian Keluarga dengan Balita Stunting di Kelurahan Bulak Banteng Kota Surabaya - Dwi Ernawati (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2019)
Stunting is suffered toddler from growth failure due to chronic malnutrition that the child looks shorter than their age. Stunting has encountered in Bulak Banteng district Surabaya, one of the causes of stunting family is family isn’t able to carry children with stunting out independently, yet. The purpose of this study is to analyze the correlation of knowledge with family independence in stunting children at Bulak Banteng district Surabaya. The design of this study was observational analytic with cross sectional approach. Sample of this study is 124 families that had 2-5 years-old children with stunting. Sampling technique is simple random sampling. Independent variables was knowledge, measured by structured questionnaire. Dependent variable is family independence measured by Friedman's independent self-observation sheet. Analysis test in this study is using the Spearman rho test ρ = 0.05. The results of this study indicated that knowledge is related to family independence in stunting children with ρ = 0,0009. Stunting can be prevented and treated independently if the family active to participates of PIS-PK program carried out by health workers in Bulak Banteng district Surabaya to prevent and provide stunting management that is scheduled and routinely by utilizing family health profile information data. Keywords : Knowledge, Family Independence, Stunting